C-Reactive Protein Testing to Guide Antibiotic Prescribing for COPD Exacerbations - Fatima, Roshaan; Mahmud, Rizwan; Manzoor, Shahzad (Biological and Clinical Sciences Research Journal, 2025)
Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are commonly treated with antibiotics, although bacterial infection is not present in all cases. Overprescription contributes to antimicrobial resistance and unnecessary healthcare costs. Biomarkers such as C-reactive protein (CRP) may help clinicians guide more appropriate antibiotic use. Objective: To determine whether C-reactive protein (CRP)–guided antibiotic prescribing reduces antibiotic use in patients with acute exacerbations of chronic obstructive pulmonary disease. Methods: A randomized controlled trial was conducted at Benazir Bhutto Hospital in Rawalpindi from 11 June 2025 to 11 November 2025. A total of 174 patients aged ≥40 years with confirmed COPD presenting with AECOPD were enrolled and randomly allocated into two groups (87 patients each). The intervention group received CRP-guided care in which point-of-care CRP testing was performed, and antibiotics were prescribed only when CRP levels exceeded 20 mg/L. The control group received standard care based on clinical assessment and physician judgment without CRP testing. Patients were followed for four weeks to evaluate antibiotic prescription rates. Data were analyzed using SPSS version 25.0. Categorical variables were compared using the Chi-square test and continuous variables using the Student’s t-test. A p-value <0.05 was considered statistically significant. Results: Baseline demographic and clinical characteristics were comparable between the two groups. At the initial consultation, antibiotics were prescribed to 36.7% of patients in the CRP-guided group compared with 77% in the standard care group (χ²=28, p<0.0001). At four-week follow-up, antibiotic prescription rates were 10.3% in the CRP-guided group and 89.6% in the standard care group (χ²=109, p<0.0001), demonstrating a marked reduction in antibiotic utilization in the intervention group. Conclusion: CRP-guided antibiotic prescribing significantly reduces antibiotic utilization among patients with acute exacerbations of COPD compared with standard clinical judgment alone. Incorporating CRP testing into routine clinical practice may help promote rational antibiotic use in the management of AECOPD.